2017
DOI: 10.1111/aec.12520
|View full text |Cite
|
Sign up to set email alerts
|

No signs of Na+/K+ATPase adaptations to an invasive exotic toxic prey in native squamate predators

Abstract: Invasions by exotic toxic prey, like the release of the South American cane toad (Bufo (Rhinella) marinus) to the toad-free Australian continent in 1935, have been shown to result in massive declines in native predator numbers. Due to minor nucleotide mutations of the Na + /K + -ATPase gene most Australian squamate predators are highly susceptible to cane toad toxin. However, in spite of this, predators like yellow-spotted goannas (Varanus panoptes) and red-bellied black snakes (Pseudechis porhyriacus) still p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Hakodate have been exposed for sufficient time to potentially allow such adaptation. Indeed, behavioral aversion and toxin resistance have evolved within a lesser timeframe for native snakes exposed to toxic invasive cane toads in Australia (~23 generations: Phillips & Shine, 2006), although the mechanism of toxin resistance is unclear (Pinch et al, 2017; see also Dobler et al, 2012;Mohammadi et al, 2016;Ujvari et al, 2015). In contrast, neither behavioral aversion nor toxin resistance has evolved in native Australian frog tadpoles within ~24 generations of exposure to cane toads (Crossland & Alford, 1988;Easteal, 1986), suggesting that amphibians may require a longer timeframe to adapt to novel toxic prey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hakodate have been exposed for sufficient time to potentially allow such adaptation. Indeed, behavioral aversion and toxin resistance have evolved within a lesser timeframe for native snakes exposed to toxic invasive cane toads in Australia (~23 generations: Phillips & Shine, 2006), although the mechanism of toxin resistance is unclear (Pinch et al, 2017; see also Dobler et al, 2012;Mohammadi et al, 2016;Ujvari et al, 2015). In contrast, neither behavioral aversion nor toxin resistance has evolved in native Australian frog tadpoles within ~24 generations of exposure to cane toads (Crossland & Alford, 1988;Easteal, 1986), suggesting that amphibians may require a longer timeframe to adapt to novel toxic prey.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, predator resistance to bufonid toad toxins is associated with genetic modification of the sodium-potassium-pump (Na + /K + -ATPase: Mohammadi et al, 2016: Ujvari et al, 2015. However, such genetic adaptation has not occurred in red-bellied black snakes (Pinch et al, 2017), suggesting that another mechanism of toxin resistance may have evolved in this species. Although invasive species are likely to be powerful agents of selection on native biota (Stockwell et al, 2003), research in this area is relatively scarce, and particularly for native vertebrates, the evolutionary impacts of invasive species are only beginning to be understood (Cattau et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Even a tiny genetic change can confer high resistance, and many lineages of predators from the toads’ native range exhibit that capacity 35 , 36 . We might thus expect strong selection for these genetic changes in monitor lizards in areas long colonised by toads, but no such changes have evolved 18 . If indeed monitors refuse to eat toads (as suggested by our study), that behaviour removes any advantage to physiological tolerance to the toads’ poisons—and hence, eliminates selection for genetic changes that confer toxin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Lethal toxic ingestion of toads causes rapid declines in varanid abundance (lizards trained to avoid toads have higher survival 13 ); and two studies in eastern Australia have reported that monitors in toad-infested areas (but not toad-free areas) refuse to consume toad flesh 14 , 15 . Hence, it seems likely that monitors survive toad invasion by developing taste aversion (the association of cues with symptoms arising from spoiled or toxic substances 16 ) rather than by shifts in morphology (monitors can tear prey items apart, so head size does not constrain ingestible prey size 17 ) or physiology (toad-sympatric monitors lack genetic changes that confer toxin resistance 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In perhaps the most convincing example affecting animal communities, V. panoptes populations declined by >90% within three years post-toad arrival, and could no longer be detected 10 years later (Doody et al 2009; 2017; see also Pinch et al 2017). Because V. panoptes is a top predator in the tropical savannah ecosystem, its declines have facilitated its prey: several species showed population increases rather dramatically soon after its toad-induced demise, including pig-nosed turtles (Carettochelys insculpta), freshwater crocodiles (Crocodylus johnstoni), Gilberts' dragons (Amphibolorus gilberti), and common treesnakes (Dendrelaphis punctulatus) (Doody et al 2006;2015a;Webb & Manolis 2010).…”
Section: ; Phillips Et Al 2010)mentioning
confidence: 99%